Coincident Observations by the Kharkiv IS Radar and Ionosonde, DMSP and Arase (ERG) Satellites, and FLIP Model Simulations: Implications for the NRLMSISE‐00 Hydrogen Density, Plasmasphere, and Ionosphere - D. V. Kotov; P. G. Richards; V. Truhlík; O. V. Bogomaz; M. O. Shulha; N. Maruyama; M. Hairston; Y. Miyoshi; Y. Kasahara; A. Kumamoto; F. Tsuchiya; A. Matsuoka; et al. (Geophysical Research Letters)
Abstract This paper reports the results of ionosphere and plasmasphere observations with the Kharkiv incoherent scatter radar and ionosonde, Defense Meteorological Satellite Program, and Arase (ERG) satellites and simulations with field line interhemispheric plasma model during the equinoxes and solstices of solar minimum 24. The results reveal the need to increase NRLMSISE‐00 thermospheric hydrogen density by a factor of ~2. For the first time, it is shown that the measured plasmaspheric density can be reproduced with doubled NRLMSISE‐00 hydrogen density only. A factor of ~2 decrease of plasmaspheric density in deep inner magnetosphere (L ≈ 2.1) caused by very weak magnetic disturbance (Dst > −22 nT) of 24 December 2017 was observed in the morning of 25 December 2017. During the next night, prominent effects of partially depleted flux tube were observed in the topside ionosphere (~50% reduced H+ ion density) and at the F2‐layer peak (~50% decreased electron density). The likely physical mechanisms are discussed.